The study of lepidocyclina (eulepidina) (foraminifera) from middle Oligocene to lower Miocene of South Albania - MYFTARI, S.; BARO, M.; MYFTARI, B. (Bulletin of the Geological Society of Greece, 2018)
There are studied too many samples from Ionian Zone (geological outcrops and drilling wells) and Koma depression containing Larger Foraminifers, Lepidocyclina (Eulepidina) subgenus. For their study, determination to species level, biometrie and counting measurements known in literature are used. According to proposal (for Mediterranean region) we suggest that in south Albania also can be separated the following species and subspecies: - Lepidocyclina-(Eulepidina) formosoides DOUVILLE R. - Lepidocyclina-(Eulepidina) dilatata (MICHELOTTI) - Lepidocyclina-(Eulepidina) dilatata (MICHELOTTI) var concentrica SILVESTRI For the specimens of microsphaeric generation (B-Form, diameter more than 5 centimeter) maintained the typological concept of classification and were attributed to the species Lepidocyclina (Eulepidina) elephantine LEMOINE and DOUVILLE (1904). They are given briefly the deposition conditions of the shells of this subgenus in flysch (Ionian Zone and mollasic deposits (Korria depression) Middle Oligocene- Lower Miocene age. The paper has been accompanied by means 3 plates.